Metaanalisis korelasi antara motivasi dengan adopsi inovasi pertanian Metaanalysis of correlation between motivation and adoption of agriculture innovation - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT: Some researches used the same variables as independent or dependent variables often have different conclusion. For example, a research has a conclusion that attitude toward new technology influence significantly the adoption of the technology, but another researcher has conclusion that attitude does not influence the adoption, etc. Metaanalysis is useful to understand why results of the researches are imperfect, and moreover one maybe find new variables that can lead finding new theory. This analysis want to try to understand problem on correlation between motivation and adoption of agriculture inovation from ten thesis S2 and SI.